2022
DOI: 10.1186/s12951-022-01446-1
|View full text |Cite
|
Sign up to set email alerts
|

SHED-derived exosomes promote LPS-induced wound healing with less itching by stimulating macrophage autophagy

Abstract: High-quality cutaneous wound healing is associated with rapid wound closure and a comfortable healing process. Currently, exosomes derived from mesenchymal stem cells displayed a prominent therapeutic effect on skin wound closure. But the therapeutic approaches for wound itching are very limited in clinical. Stem cells from human exfoliated deciduous teeth (SHED) may offer a unique exosome resource for cell-free therapeutics in potential clinical applications. Here, we investigated the common mechanisms underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Previous studies have suggested the involvement of autophagy in immune regulation (Jiang et al, 2019;Wang et al, 2022b;Xie et al, 2022). The autophagic decomposition of cyclic GMP-AMP synthase could be astricted by TRIM14, thus enhancing congenital immunity (Chen et al, 2016).…”
Section: Involvement Of Ncrna-autophagy Axis In Immune Regulationmentioning
confidence: 97%
“…Previous studies have suggested the involvement of autophagy in immune regulation (Jiang et al, 2019;Wang et al, 2022b;Xie et al, 2022). The autophagic decomposition of cyclic GMP-AMP synthase could be astricted by TRIM14, thus enhancing congenital immunity (Chen et al, 2016).…”
Section: Involvement Of Ncrna-autophagy Axis In Immune Regulationmentioning
confidence: 97%
“…Exosome nanoparticles were purified by several ultracentrifugation and filtration steps according to the previously published procedures. [8] Briefly, SHEDs and human adult dental pulp stem cells (DPSCs) at passages 3-6 were utilized for the exosome isolation. The SHEDs and DPSCs were cultured in a complete medium with the fetal bovine serum for 48 h (with depletion of exosomes by 2 h centrifugation at 100 000g), culture supernatants of SHEDs and DPSCs were collected.…”
Section: Isolation and Characterization Of Shed-exo Bio-nanoparticlesmentioning
confidence: 99%
“…SHEDderived exosomes containing miR-1246 also enhanced autophagy by regulating macrophage function through the AKT, ERK1/2, and STAT3 signaling pathways. Therefore, SHED-derived exosomes promote wound healing with less itching in an LPS-induced wound model by stimulating macrophage autophagy, which has implications for the treatment of inflammatory wound healing [50].…”
Section: Other Therapeutic Effects Of Shedmentioning
confidence: 99%